The Effectiveness of Trauma-Focused Psychodrama in the Treatment of PTSD in Inpatient Substance Abuse Treatment - Giacomucci, Scott; Marquit, Joshua (Frontiers in Psychology, 2020)
This single group pretest-posttest study explores the effectiveness of trauma-focused psychodrama in the treatment of post-traumatic stress disorder (PTSD) at an inpatient addiction treatment center. The results contribute to the limited research bases of both psychodrama and PTSD treatment outcomes in inpatient addiction treatment. The present study supports the potential effectiveness of two trauma-focused psychodrama models, the Therapeutic Spiral Model and the Relational Trauma Repair Model. Findings of the research demonstrate clinically significant reductions in overall PTSD symptoms (over 25% change) and each PTSD symptom cluster (i.e., re-experiencing and intrusion, avoidance and numbing, and hyper-arousal). Additionally, patient satisfaction exit survey data support overall treatment effectiveness and highlight its tolerability, and capacity for establishing emotional safety, connection, and group cohesion. Patients even described the trauma-focused psychodrama treatment approach as enjoyable and helpful. Overall, the results of this study are promising, and support continued clinical application of trauma-focused psychodrama treatment with other subpopulations diagnosed with PTSD. However, the ability to isolate effects of trauma-focused psychodrama in this study is compromised due to the absence of a control group and participants’ involvement in other inpatient treatment services.